1151 Patients' preferences for anti-epileptic drugs (aeds). (1st December 2017) - Holmes, Emily; Baker, Gus; Jacoby, Ann; Ring, Adele; Marson, Anthony; Hughes, Dyfrig
Abstract : Objectives: To identify preferences for outcomes of antiepileptic drugs (AEDs) that patients consider important and, to investigate the impact of patient preferences on the ranking of AEDs, as indicated by a clinical trial. Methods: Adult patients with epilepsy completed a web-based questionnaire containing a discrete choice experiment. Patients made choices between hypothetical pairs of AEDs described by varying levels of clinical efficacy and treatment-related adverse events (AEs). Data were analysed using a random effects logit model. Women with the potential to become pregnant were analysed separately. Utility and probability of uptake for existing AEDs were derived using preference weights and published clinical event data. Results: Patients (n=414) had stronger preferences for reducing the risk of AEs than improving treatment benefit. In return for a 1% improvement in 12 month remission, the maximum acceptable risk of adverse events was: depression 0.31%, memory problems 0.30%, aggression 0.25%; and for women with the potential to become pregnant: depression 0.56%, memory problems 0.34%, and foetal abnormality 0.20%. The rank ordering of AEDs differed when patient preferences were considered. Conclusion: Exploring what patients consider important in measuring AED effectiveness will assist in supporting adherence, and ensure clinical services are focused on patient-defined needs.